The Concept, Goals, And Objectives of the Digital Economy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Currently, in many developed countries, the digital economy has a significant impact on the factors of their development, and also plays an important role in the life of society. In this article, you can find answers to such questions about the digital economy as "What is the digital economy?", "The tasks and goals of the digital economy", Hardnesses to the development of the digital economy in Uzbekistan.